APPLICATION OF AZOLLA FERTILIZER ON VEGETATIVE GROWTH RED CHILI PLANT (CAPSICUM ANUUM [L.]) - Eko Abadi Novrimansyah (International Journal of Multidisciplinary Reseach, 2026)
Red chili production in Lampung Province has declined, and low soil fertility is considered one of the main causes. Soil fertility may be improved by combining organic and inorganic fertilization. Azolla is an aquatic fern that fixes atmospheric nitrogen and releases it slowly into the soil, while also improving the biological, physical, and chemical properties of the soil. This study aimed to determine the effect of combined Urea and Azolla application on the vegetative growth of red chili cultivar TM 999. The research was conducted in Bandar Lampung from February to May 2025 using a single-factor treatment design arranged in a Randomized Complete Block Design with four replications. Homogeneity of variance was tested using Bartlett's test and model additivity using Tukey's test, followed by analysis of variance and mean separation with the Least Significant Difference test at the 5% level. The treatments consisted of six combinations of Azolla and Urea ranging from 0% to 100% Azolla. The results showed that the combination of 40% Azolla and 60% Urea increased the plant height of red chili cultivar TM 999 and did not differ significantly from the application of 100% Urea.